FWC543: Popular Writing / College of Creative Arts - UiTM, College of Creative Arts (2023)
Popular writing refers to 'casual' or 'informal' writing on issues such as technology, celebrities, political news and opinions, video games and computer games, entertainment such as music and movies, as well as on issues such as finance and law. In addition, popular writing also involves writings on psychology and racial issues. It aims to take a more relaxed, loose and informal approach towards discussing current issues within society of the time. Students will be exposed to the various forms of popular writing as a means of providing a simpler approach to expressing various points of views. It is about writing in popular culture.